ANALISIS BREAK EVEN POINT USAHA PENGGEMUKAN KAMBING MILIK BAPAK SULTON DESA SIDOREJO KECAMATAN PONGGOK KABUPATEN BLITAR - Aan Jiwo Prasetyo; Nita Opi A.K; Sri Setyowati (Universitas Islam Balitar, 2017)
This research formulates one problem hit analisis finishing effort goat on Sulton's Father ranch Sidorejo's Village Ponggok's district Blitar's Regency. Expected by this research can become consideration for cattlemen to take a decision deep fattening's effort management goat. This research is done at Fathers own ranch Sulton lies at Pancir's Orchard Sidorejo's Village Ponggok's district Blitar's Regency. Data is taken from one fattening's period which is 3 months utilize case study and data method at fetching descriptive ala and quantitative.Capital constitutes a number goods, service, and money to start an effort stage. Production cost constitutes all cost that issued by producer to result a goods or service product. Differentiated production cost becomes two kinds which is fixed cost( fixed cost ) and offbalance cost( variable cost ). Immanent cost all cost that don't hinge on outgrows its little production. Cost is not immanent all big cost its little cost hinges on outgrows its little production. Of this research is acquired data total production cost as big as Rp 11.977.323, totaled acceptance as big as Rp 16.105.00 so gets to be gotten by Rp's gains 4.127.600 about production periods, gain a moon Rp 1.375.000. Mean while BEP is production it is 16.24 and BEP is price it is Rp 598.866. Base data that at gets from research result, can know effort gain zoom finishing goat and gets to be seen by break even point's break even point or dot finishing effort goat with aught.Keyword : Break even point, Fatenning